Superparamagnetic nanocomposite of magnetite and activated carbon for removal of dyes from waste water - Thakuria, Pankaj; Joy, Pattayil Alias (Nanoscience and Nanotechnology Letters, 2009)
Nanocomposite of superparamagnetic Fe(3)O(4) and activated carbon (AC) is synthesized at room temperature and characterized by various techniques. Magnetic measurements indicated that the Fe(3)O(4) nanoparticles are isolated by the AC particles. The magnetic fluid obtained by dispersion of the nanocomposite in water is found to be relatively stable. The dispersion is found to be very efficient for the removal of methylene blue dye from water. Thus, the nanocomposite is highly suitable for removing dissolved dyes and other contaminants from waste water by a simple magnetic separation process after adsorption on AC.
Keywords: Magnetic Separation; Nanocomposite; Superparamagnetism; Water Purification